Inhibitory Effect of Veterinary Antibiotics on Denitrification in Groundwater: A Microcosm Approach - Mahtab Ahmad; Meththika Vithanage; Kangjoo Kim; Ju-Sik Cho; Young Han Lee; Young Kyoo Joo; Sang Soo Lee; Yong Sik Ok (The Scientific World Journal)
Veterinary antibiotics in groundwater may affect natural microbial denitrification process. A microcosm study was conducted to evaluate the influence of sulfamethazine and chlortetracycline at different concentrations (0, 0.01, 0.1, and 1.0 mg/L) on nitrate reduction in groundwater under denitrifying condition. Decrease in nitrate removal and nitrite production was observed with the antibiotics. Maximum inhibition of nitrate removal was observed after seven days of incubation with 0.01 mg/L sulfamethazine (17.0%) and 1.0 mg/L chlortetracycline (15.4%). The nitrite production was inhibited with 1.0 mg/L sulfamethazine to 82.0% and chlortetracycline to 31.1%. The initial/final nitrate concentrations indicated that 0.01 mg/L sulfamethazine and 1.0 mg/L chlortetracycline were most effective in inhibiting activity of denitrifying bacteria in groundwater. After 12 days of incubation, the sulfamethazine biodegradation was observed whereas chlortetracycline was persistent. Sulfamethazine and chlortetracycline in groundwater could inhibit the growth and capability of naturally occurring denitrifying bacteria, thereby threatening nitrate pollution in groundwater.